1994
DOI: 10.1177/000456329403100606
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Stability in Whole Blood of 14 Commonly-Requested Hormone Analytes

Abstract: Concentrations of 14 commonly-requested plasma hormones were measured in octuplicate in each of six subjects to determine their stability when unseparated from red cells for periods up to 1 week. Most of the analytes were stable when stored in this way and although statistically significant changes were recorded, in the great majority of cases the changes seen would have no bearing on the clinical interpretation of the result. In the light of these findings, we would confidently report results of analyses for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 11 publications
3
20
0
Order By: Relevance
“…We found a significant change in ACTH plasma concentrations with time, as in other studies (1,5 ), but this change was much smaller than expected. Unlike another investigation (5 ), we studied samples not only from healthy volunteers but also from patients with high ACTH concentrations.…”
Section: Preanalytical Stability Of Adrenocorticotropic Hormone Depensupporting
confidence: 84%
See 1 more Smart Citation
“…We found a significant change in ACTH plasma concentrations with time, as in other studies (1,5 ), but this change was much smaller than expected. Unlike another investigation (5 ), we studied samples not only from healthy volunteers but also from patients with high ACTH concentrations.…”
Section: Preanalytical Stability Of Adrenocorticotropic Hormone Depensupporting
confidence: 84%
“…Adrenocorticotropic hormone (ACTH) in blood is considered highly unstable because of proteolytic degradation (1)(2)(3)(4), so storage of blood samples on ice until analysis is recommended. In clinical practice, however, this procedure may present logistical problems because most samples for ACTH measurement must be shipped from the place of sample collection to the laboratory.…”
Section: Preanalytical Stability Of Adrenocorticotropic Hormone Depenmentioning
confidence: 99%
“…Our findings were consistent with observations on the stability in EDTA plasma [19]. In whole blood, the delay in ACTH level was 97% greater than baseline values [2]. Ellis J and et al suggested that the median concentration of ACTH showed a significant decline after 18 h at 4°C [18].…”
Section: Resultssupporting
confidence: 92%
“…This is of particular importance, since using aprotinin blood collection tubes is an additional step commonly used in the sample collection process for some peptides [16,17]. We found a significant change in ACTH plasma concentrations with time, as in other studies [2,18]. Unlike another investigation [18], we assumed that some disease states could alter the blood enzyme levels and studied samples not only from healthy volunteers but also from 2 patients with high ACTH concentrations in order to detect the significant affected changes.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation